Bahan Ajar Audio Visual Penunjang Pembelajaran Mata Kuliah Tenis Lapangan - Raibowo, Septian; Fathoni, Abi Fajar; Adi, Sapto (Universitas Nusantara PGRI Kediri, 2022)
The process of learning tennis skills begins with the cognitive, associative, and automation stages. The cognitive stage is the most basic stage, so it is necessary to identify student learning styles at this stage. The learning styles that are widely used at the cognitive stage are visual and auditory learning styles. Teaching materials in the form of audio-visual can facilitate student learning styles at the cognitive stage. This research aims to develop audio-visual teaching materials for teaching tennis courses. The research method used is research and development. Then a sample was taken using a simple random sampling technique of 25% representing the entire population. So that the research subjects obtained as many as 47 students. The research instrument is a closed questionnaire that has obtained validation from experts. Questionnaires were used to retrieve response data from research subjects who had used the developed research product. Then the data were analyzed with the help of CAQDAS software. The study results were that an average of more than 90% of the research subjects gave positive responses to the tennis court audio-visual teaching materials, which were seen from the responses of the research subjects to the indicators in the developed teaching materials. So, it can be concluded that the audio-visual teaching materials for teaching tennis courses are feasible to use.